Intensive forest harvesting increases susceptibility of northern forest soils to carbon, nitrogen and phosphorus loss. Issue 1 (19th June 2017) - Hume, Alexandra M.; Chen, Han Y. H.; Taylor, Anthony R.
Abstract: Understanding the impact of forest harvesting is critical to sustainable forest management, yet there remains much uncertainty regarding how harvesting affects soil carbon (C), nitrogen (N) and phosphorus (P) dynamics. Here, we conducted a global meta‐analysis of 808 observations from 49 studies to test the effects of harvesting on the stocks and concentrations of soil C, N and P and C:N:P ratios relative to uncut control stands. With all harvesting intensities combined, C stock was unaffected by harvesting in either the forest floor or mineral soil, while harvesting reduced forest floor [C], [N] and [P] and C:N ratio, increased the mineral soil [C] and C:N ratio, but reduced mineral soil N stock. The impacts of harvesting on forest floor C and N stocks, C:P and N:P and mineral soil [C] and [N] changed from no effects by partial, stem‐only and whole‐tree harvesting (WTH) to significantly negative effects by the harvesting coupled with fire. Stem‐only and WTH similarly reduced forest floor [P]. The negative effects of harvesting were most pronounced in conifer stands. Soil [C], [N] and C:N decreased with time since harvesting, but soil [P] did not, resulting in an increase in forest floor N:P. Synthesis and applications . Our findings highlight the importance of harvest intensity and rotation length on long‐term soil nutrient availability when managing forests. Furthermore, the lag in the recovery of phosphorus concentration following harvesting may indicate a decoupling of the phosphorus cycle from those of carbon and nitrogen, and a potential concern in managed forests. Abstract : Our findings highlight the importance of harvest intensity and rotation length on long‐term soil nutrient availability when managing forests. Furthermore, the lag in the recovery of phosphorus concentration following harvesting may indicate a decoupling of the phosphorus cycle from those of carbon and nitrogen, and a potential concern in managed forests.